Kritik Sosial Dalam Lirik Lagu (Analisis Wacana Lagu Maju Dari .Feast) - Tirta, Danu; Sari, Sapta; Dianthi, Martha Heriniazwi (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Feast is a band that expresses social criticism through songs. Idealism in music, the use of words that contain figures of speech, and the themes presented make the author use the lyrics of the song